Bridging the gap: the role of the 'ART'UISM Program' in enhancing cognitive abilities and community acceptance for children with Autism - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Abdullah, Mohamad Hariri; Isa, Badrul; Michael, Valerie (Universiti Teknologi MARA, Perak, 2025)
This study evaluates the effectiveness of the 'ART'UISM: Artistic-Intuition-Autism Program' in enhancing creative expression and cognitive development in children with autism. This program has been designed to promote art as a therapeutic activity and further develop the psychomotor and cognitive skills of children with autism. Pre- and post-survey questionnaires were administered to parents/family members to measure the program's effectiveness. The study included 18 children diagnosed with Autism Spectrum Disorder. Results indicate significant improvements in colour identification, shape recognition, attention span, task completion, acquisition and learning of new activities, self-confidence, and emotional regulation. The supportive environment created by the program allowed each participant to feel safe and respected, encouraging their creative expression. Based on these results, the study demonstrates that art therapy can facilitate multifaceted development in children diagnosed with autism and positively influence society's perception and acceptance of these children.